The Concept Of Honesty In The Book Of Taisirul Khallaq Fi Ilmi Al-Akhlaq By Khafid Hasan Al-Mas'udi And Its Relevance To Character Education - Mujib Abdur Rohman; M Ahsanul Husna; Ubbadul Adzkiya'; Ali Imron; Imam Khoirul Ulumuddin (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
Honest is reporting something in accordance with the goods. Meanwhile, lying is reporting something that is not according to understanding. Thus, someone who states that it is not in accordance with the truth and or does not admit something is in accordance with the truth, that person is not honest or dishonest. Sheikh Hafidz Hasan Al-Mas'udi has specifically explained the factors that make a person behave honestly, including: reason, religion and self-respect. The research objective was to determine the concept of honesty in the holy book khallaq fi ilmi al-akhlaq, to ​​analyze the relevance of the concept of honesty in the taisirul khallaq fil ilmi akhlak book with the latest character education theory. This research was conducted using the library research method. Collecting data by following the data by looking for data about something or variables in the form of notes, books, books, journals and other written objects. The data analysis method used content analysis. The conclusions of this study indicate: (1) According to Sheikh Hafidz Hasan Al-Mas'udi in his book Taysirul Khallak Fil Ilmi Al-Akhlak being honest is reporting something that is in accordance with reality. A three-stage performance to get someone to behave honestly, including: reason, religion, and self-respect. (2) There is a connection between the concept of honesty in the book Taysirul Khallaq Fil Ilmi Al-Akhlak with the theory of character education. Muchlas Samani and Hariyanto explained that the Minister of National Education has chosen core values, one of which is honesty. There are two stages to making someone behave honestly, including: reason and self-respect. But what is different here is that in the book Taysirul Khallaq Fil Ilmi Al-Akhlak, there are religious factors that influence a person's character to behave honestly. Because religion is a new human life and provision for social life.